2023
DOI: 10.1097/inf.0000000000003894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics of Children Infected With Coronavirus Disease 2019 Between Omicron Variant BA.5 and BA.1/BA.2 in Japan

Abstract: Background: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants has dramatically altered the clinical profile of pediatric coronavirus disease 2019 (COVID-19). In Japan, we experienced a pandemic of omicron subvariant BA.1/BA.2 from January through June 2022. However, after the emergence of BA.5 in early July 2022, the number of children hospitalized with COVID-19 increased dramatically in Japan. Methods: We collected data on monthly numbers of cases and clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…21 In addition, infection with Omicron BA.1 and BA.2 subvariants was associated with more frequent upper respiratory symptoms and neurological complications. 6,8,21 Similar observations were made by authors from South Korea, who documented a higher proportion of patients with fever (89.9%), febrile seizures (8.8%) and croup (13.4%). 9 In our cohort, fever was significantly more frequent during LO period (87% compared to 79% during EO), but the prevalence of febrile seizures was low and did not differ according to the analyzed periods (1.5% during LO, and 0.87% during EO).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…21 In addition, infection with Omicron BA.1 and BA.2 subvariants was associated with more frequent upper respiratory symptoms and neurological complications. 6,8,21 Similar observations were made by authors from South Korea, who documented a higher proportion of patients with fever (89.9%), febrile seizures (8.8%) and croup (13.4%). 9 In our cohort, fever was significantly more frequent during LO period (87% compared to 79% during EO), but the prevalence of febrile seizures was low and did not differ according to the analyzed periods (1.5% during LO, and 0.87% during EO).…”
Section: Discussionsupporting
confidence: 84%
“…6 The authors concluded that the emergence of BA.5 had a more severe impact on children, as the incidence of hospitalizations and neurological complications (including febrile seizures with prevalence of 27.9% vs. 7.0% during BA.1/BA.2) increased significantly. 6 Thus, despite the overall good prognosis for children suffering from COVID-19 during LO, it should be considered that the impact of the new Omicron subvariants on pediatric patients seems to be different than in adults, in which better clinical outcomes were observed according to the data from SARSTer database. 25 In addition, selected cases, in particular older children with comorbidities and with confirmed radiological pulmonary lesions in the course of SARS-CoV-2 infection, should be managed with precaution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 However, regarding the efficacy of vaccines and associated adverse reactions in children, the Japan Pediatric Society had to make recommendations based on overseas data alone 4 because the Japanese data were insufficient at that time. Since then, Japanese data have been accumulated, [18][19][20] but it has not yet been explained by the government to citizens in an easy-to-understand manner. Such accurate data are exactly what Japanese guardians desire to receive.…”
Section: Guardians Who Had Had One Of Their Children Vaccinated With ...mentioning
confidence: 99%